Enhancing the Efficiency of Organic Photovoltaics by a Photoactive Molecular Mediator (Solar RRL 1∕2018). Issue 1 (15th January 2018) - Yang, Bin; Kolaczkowski, Matthew A.; Brady, Michael A.; Keum, Jong K.; Browning, James F.; Chen, Teresa L.; Liu, Yi
Abstract : In the search for high efficiency organic solar cells, additives often play an important role in improving the film morphology. The vast majority of the currently used additives are liquids that, while often effective, evaporate or migrate over time lowering the stability of the device. Herein, Liu et al. (article No.1700208 ) report a solid photoactive molecular mediator, namely N(BAI)3, that could be employed to replace the liquid additives to tune the morphology of bulk heterojunction films for improved device performance. The N(BAI)3 mediator not only resides in the active films to fine tune the phase morphology, but also contributes to the additional absorption of the active films, leading to ∼ 11% enhancement of power conversion efficiency of P3HT:PC60 BM devices. In‐depth studies on the nanoscale morphologies using X‐ray and neutron scattering techniques suggest that the use of 1 wt% N(BAI)3 effectively tunes the packing of P3HT, presumably through balanced Π‐interactions endowed by its large conjugated Π surface, and promote the formation of a PC60 BM‐rich top interfacial layer. These findings open up a new way to tailor the phase morphology by photoactive molecular mediators in organic photovoltaics.